2014
DOI: 10.9790/3013-0401008016
|View full text |Cite
|
Sign up to set email alerts
|

The Effect Of Roselle Extract (Hibiscus sabdariffa Linn.) On Blood Glucose Level And Total Antioxidant Level On Diabetic Rat Induced By Streptozotocin

Abstract: : Roselle (Hibiscus sabdariffa Linn.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Oral administration of H. sabdariffa extract, as well as Glibenclamide significantly decreased blood glucose levels in a dose dependent manner. Our results were in line with several studies using H. sabdariffa extract to manage blood glucose level in rats [17,29,30]. To assess pancreas capacity to produce insulin after treatment with H. sabdariffa extract in alloxan-induced diabetic rats, OGTT was determined at the end of study.…”
Section: Discussionsupporting
confidence: 89%
“…Oral administration of H. sabdariffa extract, as well as Glibenclamide significantly decreased blood glucose levels in a dose dependent manner. Our results were in line with several studies using H. sabdariffa extract to manage blood glucose level in rats [17,29,30]. To assess pancreas capacity to produce insulin after treatment with H. sabdariffa extract in alloxan-induced diabetic rats, OGTT was determined at the end of study.…”
Section: Discussionsupporting
confidence: 89%
“…Roselle has been proven to rich in nutrients like vitamins and polyphenol that might promote antioxidant properties (Jabeur et al, 2017;Riaz and Chopra, 2018). The roselle calyxes extract was found to promote health benefit as an anticancer and capable of reducing the chronic disease for instance hypertension, diabetes mellitus and cardiovascular disease (McKay et al, 2010;Akim et al, 2011;Mardiah et al, 2014;Formagio et al, 2015). Thus, it demonstrated that roselle juice could be an excellent carrier in developing functional beverages with GA as a prebiotic source.…”
Section: Introductionmentioning
confidence: 99%
“…Aqueous extracts of red and white roselle were reported to reduce hyperglycemia through the inhibition of α-amylase and α-glucoside in an in vitro study as the enzymes responsible for carbohydrate hydrolysis, thus attenuating the occurrence of chronic diseases, mainly DM and CVDs [ 78 ]. Moreover, according to a study by Mardiah and colleagues [ 79 ], roselle aqueous extract given to type I diabetic rats at a dose of 288 mg/200 g body weight daily for 20 days reduced blood glucose due to the improvement of the number of β cells producing insulin in pancreatic cells. A study by Ajani et al [ 12 ] proved that roselle aqueous extract was able to reduce the percentage of glucose in the blood in type I diabetic models given 200 and 500 mg/kg of the extract for 28 days.…”
Section: Roselle In the Attenuation Of Cardiovascular Diseases Risk F...mentioning
confidence: 99%